2020
DOI: 10.31695/ijasre.2020.33862
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Different Fertilizers Effects on Maize Growth Parameters

Abstract: Lower soil fertility was identified as a major problem affecting crop yield in Burundi, especially at Bihunge, a hill of Matongo commune Kayanza province. An experiment was therefore carried out with five treatments to assess the effective and economically affordable treatment on maze growth parameters improvement. The experimental has considered five treatments: the control (T1); Compost from maize residues + mineral adjuvant (T2); Compost from maize residues + organic adjuvant based on Calliandra calothyrsus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Significant effects (p < 0.001) of tested fertilizer treatments were observed for maize grain yields (GY), above ground biomass (AGB) and root biomass (RB). Maize yields followed a decreasing order: T 4 (5 777 kg/ha) ≈ T 5 ( In a previous paper on this specific investigation topic based on growth parameters [62], it was reported that the best treatments T 4 (farm manure+45-60-30) and T 5 (maize stover co-composted with Calliandra calothyrsus Meisn green manure+45-60-30) were not significantly different from each other. However, they were significantly superior to T 1 (Control), T 2 (maize stover co-composted with mineral fertilizers and T 3 (maize stover co-composted with Calliandra calothyrsus Meisn green manure).…”
Section: Maize Yields Root and Shoot Biomassmentioning
confidence: 93%
See 1 more Smart Citation
“…Significant effects (p < 0.001) of tested fertilizer treatments were observed for maize grain yields (GY), above ground biomass (AGB) and root biomass (RB). Maize yields followed a decreasing order: T 4 (5 777 kg/ha) ≈ T 5 ( In a previous paper on this specific investigation topic based on growth parameters [62], it was reported that the best treatments T 4 (farm manure+45-60-30) and T 5 (maize stover co-composted with Calliandra calothyrsus Meisn green manure+45-60-30) were not significantly different from each other. However, they were significantly superior to T 1 (Control), T 2 (maize stover co-composted with mineral fertilizers and T 3 (maize stover co-composted with Calliandra calothyrsus Meisn green manure).…”
Section: Maize Yields Root and Shoot Biomassmentioning
confidence: 93%
“…Generally, pH values situated between 6 and 8 are indicative of mature compost [62]. Immature compost with low pH values contain higher concentrations of phytotoxic organic acids with the risks of adversely decreasing crop germination and plant growth [33].…”
Section: Characteristics Of the Organic Materials Used In The Studymentioning
confidence: 99%
“…Research on Calliandra compost shows that Calliandra is one of the plants that has the ability to fix nitrogen better than other legum plants [30]. Research in maize shows that Calliandra humus is able to increase maize yields [31].…”
Section: Introductionmentioning
confidence: 99%